ФОРМУВАННЯ ОРГАНІЗАЦІЙНО-ЕКОНОМІЧНОГО МЕХАНІЗМУ ЗАЛУЧЕННЯ ІНВЕСТИЦІЙ ДО РЕГІОНУ - Сабадаш, Віктор; Петровська, Світлана; Петровський, Михайло (Mechanism of an economic regulation, 2017)
Recently, the situation with attraction of investment to the regions of Ukraine has significantly changed for the worse because of the social and economic crisis, their low investment attractiveness, high risk and lack of guarantees for investors. This situation brings up to date the issues of elaborating an efficient organizational and economic mechanism for attracting investment to the region, which would combine not only financial and economic and legal elements, but also environmental instruments. During the study the organizational and economic mechanism for attracting investment to the region, which includes conditions, regulation and the range of organizational and economic instruments for the regulation of the investment policy has been elaborated. The instruments involved in the mechanism are grouped into functional blocks: subsidies; guarantees; tariff rates, prices; programs, plans; regulations; benefits; taxes; organizational arrangements. The key environmental elements are environmental taxes, natural resources use charges, subsidies for implementation of environmental programs and plans, state benefits and state support of environmentally sustainable production, state guarantees for attraction of environmental investments, environmental norms and standards for product certification. Their intended use is to promote the development of industrial and regional markets and to improve the efficiency of the regional investment policy.